Wind-induced torsional loads and responses of tall buildings - Singh A.; Kontoni D.-P.N.; Mandal S. (My University, 2025)
High-rise structures are prone to wind-induced forces. Wind load can be resolved into three parts: along-wind load, across-wind load, and torsional wind load. There are well-developed and reliable methods for calculating wind-induced loads in the along-wind direction for tall buildings. Numerous methods are also available to estimate the across-wind load, but this is not the case for the wind-induced torsional load. Researchers have extensively investigated the torsional behavior of tall buildings using wind tunnel experiments and full-scale investigations. This paper attempts to compile the current understanding of the wind-induced torsional response of tall buildings. The present study contributes to realizing the effects of wind-induced torsional loads on tall buildings and gives an in-depth understanding through a comparison of past studies. © 2024 MIM Research Group. All rights reserved.